IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MISKIN DI KELURAHAN KAPALO KOTO DIBALAI KECAMATAN PAYAKUMBUH UTARA - Yossy Handayani; Hermawati Hermawati; Alkhendra Alkhendra (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Well-being Social life is a condition in which a person can meet his needs and can adapt well to his environment. In improving the welfare of the poor who are unable to get a quality education, difficulties in financing health, lack of social security and protection towards families and the lack of fulfilling the needs for food, clothing, and housing the government issued PKH to improve the welfare of the poor. Some of the problems in the implementation of PKH in the Kapalo Koto sub-district are in the Payakumbuh sub-district, North Payakumbuh sub-district, namely the implementation of PKH and the achievement of targets in improving the welfare of the poor. This research is a field research using a descriptive qualitative method. The data sources for this research were PKH participants, coordinators, and PKH assistants. Data collection through observation and interviews. The data analysis technique used is data reduction, data presentation, and conclusion. The results of this study indicate that; first, the implementation has been carried out very well, it can be seen from the form of assistance provided by the companion in changing the KPM mindset so that it is more productive and creative. Second, PKH target achievement can be seen from the level of achievement of the policy itself, its implementation, targets, and environment. In achieving the targets, not all of them are correct, this is due to the lack of in-depth monitoring of KPM and the presence of people closest to them to get PKH assistance.